2022
DOI: 10.1021/acs.est.1c08860
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Fasting Blood Glucose Level to Short-Term-Exposed Particulate Constituents and Pollution Sources: Results from a Multicenter Cross-Sectional Study in China

Abstract: Ambient PM2.5 (fine particulate matter with aerodynamic diameters ≤ 2.5 μm) is thought to be associated with the development of diabetes, but few studies traced the effects of PM2.5 components and pollution sources on the change in the fasting blood glucose (FBG). In the present study, we assessed the associations of PM2.5 constituents and their sources with the FBG in a general Chinese population aged over 40 years. Exposure to PM2.5 was positively associated with the FBG level, and each interquartile range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…While some research has reported nonsignificant or negative associations between PM 2.5 exposure and sex hormone levels ( 3 ), these discrepancies may be attributable to varying PM 2.5 concentration levels, different chemical compositions, and unique characteristics of the study populations ( 5 ). It is important to note that the older adults in our study may exhibit increased sensitivity to PM 2.5 -associated health effects due to their generally poorer health status, which could impair their ability to adapt to PM 2.5 exposure ( 7 ). Additionally, there was an observed increase in testosterone levels with higher exposure to As, Sb, and Sn, but the statistical significance of these relationships was lost after applying FDR adjustments.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…While some research has reported nonsignificant or negative associations between PM 2.5 exposure and sex hormone levels ( 3 ), these discrepancies may be attributable to varying PM 2.5 concentration levels, different chemical compositions, and unique characteristics of the study populations ( 5 ). It is important to note that the older adults in our study may exhibit increased sensitivity to PM 2.5 -associated health effects due to their generally poorer health status, which could impair their ability to adapt to PM 2.5 exposure ( 7 ). Additionally, there was an observed increase in testosterone levels with higher exposure to As, Sb, and Sn, but the statistical significance of these relationships was lost after applying FDR adjustments.…”
Section: Discussionmentioning
confidence: 97%
“…The specific inclusion and exclusion criteria for participants are detailed in Supplementary Figure S1 (available at https://weekly.chinacdc.cn/ ). For more comprehensive information about the study design, refer to the published study ( 7 ). Pollutant gases such as nitrogen dioxide (NO 2 ) and ozone (O 3 ), along with PM 2.5 components like organic carbon (OC), elemental carbon (EC), water-soluble ions, and inorganic elements, were assessed using the closest fixed-site monitoring stations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of industrialization and urbanization, the demand of metal mining increases rapidly, resulting in groundwater, soil and air pollution (Ghani et al;Lv et al;Tian et al, 2022). Prolonged exposure to high concentrations of metals (such as lead, zinc, cadmium, arsenic, and antimony.)…”
Section: Editorial On the Research Topic Biogeochemistry Of Metals In...mentioning
confidence: 99%
“…PM 2.5 (fine particulate matter with a diameter ≤2.5 µm), a complex mixture, consists mainly of black carbon (BC), soil particles (SOIL), organic matter (OM), sulfate (SO 4 2− ), ammonium (NH 4 + ), and nitrate (NO 3 − ) [6,7]. Previous studies on PM 2.5 and its constituents have shown increasing evidence of adverse health consequences [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%